Effect of Product Attributes, Promotions, and Motivation on Subsidized Home Buying Decisions - Jaelani, Raditya; Yuliati, Lilik Noor; Sartono, Bagus (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Subsidized housing is a government program with the aim of meeting the housing needs of low-income peoplewhere subsidies or housing financing assistance are in the form of houses with selling prices below market prices. However, companies that develop subsidized houses must now be able to survive during increasingly fierce business competition conditions and world economic conditions that are being shaken by the Covid-19 pandemic. People's purchasing power that has decreased due to the rules for